EVALUASI KINERJA PEMERINTAHAN KAMPUNG OLEH INSPEKTORAT KABUPATEN SIAK - Dailiati, Surya; Hernimawati, Hernimawati; Sudaryanto, Sudaryanto; Zefron, Zefron (Komunitas Manajemen Kompetitif, 2023)
The purpose of this study was to describe and analyze the implementation of the role of the Siak District Inspectorate in evaluating village/village government performance and its obstacles. The research was conducted at the Siak District Inspectorate Office. The informants in this study were the State Civil Apparatuses of the Siak Regency Inspectorate Office. Data collection techniques were carried out by observation, interviews and documentation. The data that has been collected is then analyzed descriptively qualitatively. The results showed that the evaluation of the performance of the village/village administration in Siak Regency had gone well as planned by the Siak District Inspectorate. Obstacles in evaluating the performance of village/village government in Siak Regency are: the use of performance applications that have not been carried out independently by the village/village government and the leveling of development has not been in all villages/villages in terms of village facilities and infrastructure. Keywords: Evaluation, Performance, Governance, Village, Siak